Exploring factors influencing customer loyalty at Kemuning Polije Resto, Jember District - Kurniawati, Dewi; Anggraeni, Oktanita Jaya; Djamali, Raden Abdoel; Retnowati, Naning; Perlambang CNAWP, Rizal (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
Customer loyalty is vital for competitiveness in the restaurant industry, especially in local contexts where customer preferences vary. This study investigates the effects of Customer Relationship Management (CRM), service quality, and product quality on customer loyalty at Resto Kemuning Polije, Jember. A quantitative approach was used, collecting survey data from 150 regular customers. Multiple linear regression, along with t-tests and F-tests, assessed the data's validity, reliability, and significance. Results show that CRM, service quality, and product quality positively and significantly influence customer loyalty. Product quality has the strongest impact, followed by service quality and CRM. The model's adjusted R² value of 0.782 indicates that 78.2% of the variation in customer loyalty is explained by these factors. This highlights the importance of maintaining high product standards, delivering excellent service, and employing effective CRM strategies. The study provides insights into the synergy between CRM, service quality, and product quality, offering practical recommendations for restaurant managers. These include prioritising consistent product quality, personalised customer engagement, and staff training. Future research should examine additional factors like pricing and marketing strategies to deepen understanding. This study contributes to the literature on customer loyalty, emphasising the integration of quality and relationship management for sustainable retention.